Effects of bird community dynamics on the seasonal distribution of cultural ecosystem services - Graves, Rose A. (Ambio, 2018)
Biodiversity-based cultural ecosystem services (CES), such as birdwatching, are strongly influenced by biotic community dynamics. However, CES models are largely static, relying on single estimates of species richness or land-use/land-cover proxies, and may be inadequate for landscape management of CES supply. Using bird survey data from the Appalachian Mountains (USA), we developed spatial–temporal models of five CES indicators (total bird species richness, and richness of migratory, infrequent, synanthrope, and resident species), reflecting variation in birdwatcher preferences. We analyzed seasonal shifts in birdwatching supply and how those shifts impacted public access to projected birdwatching hotspots. Landscape patterns of CES supply differed substantially among indicators, leading to opposing conclusions about locations of highest birdwatching supply. Total species richness hotspots seldom overlapped with hotspots of migratory or infrequent species. Public access to CES hotspots varied seasonally. Our study suggests that simple, static biodiversity metrics may overlook spatial dynamics important to CES users. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-018-1068-1) contains supplementary material, which is available to authorized users.